Development of Macromedia Flash 8-Based Learning Media in Simulation and Digital Communication Subjects in Vocational High School - Irwanto Irwanto; Bagus Dwi Cahyono; Juanda Mitra Situmeang (Jurnal Pembelajaran Fisika, 2022)
Vocational education has a real goal, which is to prepare students to enter the world of work. The aims of this study were (1) to find out the planning stages of Macromedia flash-based learning media, and (2) to find out the feasibility of Macromedia flash-based learning media in simulation and digital communication subjects in vocational schools. This type of research is developed with the model used the V model or commonly called the verification and validation model. The system development process includes requirements analysis, requirements standards, design specifications, and program specifications. Based on the test results, it is known that the learning media based on Macromedia flash on simulation and digital communication subjects in SMKs that have been developed are suitable for use as learning media in SMKs. The average score obtained as a whole aspect of media experts was 3.58 in the very good category, material experts with a score of 3.62 in the very good category, and the student response score to Macromedia flash-based learning media was 3.89 very well. good category. good. So learning media based on Macromedia Flash 8 shows very feasible to be used as a learning medium in simulation and digital communication subjects in Vocational High Schools.Keywords: Macromedia Flash, Vocational Learning, Simulation, Digital CommunicationDOI: http://dx.doi.org/10.23960/jpf.v10.n2.202205